DOMESTIFIKASI DAN KEKERASAN SIMBOLIK TERHADAP PEREMPUAN - , Agustinus G. Raja Dasion ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Advertisement is message. That was what Roland Barthes said. It means, every sign showed in an ad (in every mass media, including television), has the meaning indeed. The meaning of an ad is in a construction. Ad is not a freely meaning reality. The meaning of an ad always derives from the domination class. By then, the meaning of ads can be changeable according to the purpose that the maker of the ad wanted to reach. Based on the understanding of that ad, researcher try to analyze the meaning of sign in Attack Easy (Kekuatan Sepuluh Tangan) ad. Researcher tries to analyze how domestification and symbolic violence to the women has shown in that ad. By that, researcher also try to analyze and breakout the myth of domestification. Researcher uses the theory of science and power of Michel Foucault and Symbolic Violence of Pierre Bourdieu to criticize domestification discourse and symbolic violence. The method used in this research is descriptive qualitative by using semiotic analysis Roland Barthes as the specific analysis. Roland Barthesâ semiotic is an analysis to find denotation and connotation meanings. Using that method of analyzing, researcher tries to criticize how the denotation and connotation meaning have shown on that ad. By finding the denotation and connotation, researcher finally fines domestification discourse and symbolic violence to the women on that ad. The result of this research shows that Attack Easy ad draws an effort of dominant class to legitimate sexual division of labor. That effort shown in every discourse in every part of life. Women constructed to live and work in domestic area (such as arrange all the house things, washing dishes, and cleaning the house). In the other hand, man works outside of domestic area (as the ad Attack Easy has shown). Women have no more freedom to be themselves. This division of labor comes from the women stereotype as week creatures physically and rationally. This is called as domestification to the women. Driving out of domestification to the women, the researcher seems to put that phenomena as a symbolic violence. Symbolic violence as Pierre Bourdieu said in his book, âOutline of a Theory of Practiceâ and âLanguage and Symbolic Powerâ as a gentle invisible form of violence, unrecognized. This form of violence attacks the integrity of women as human being. Women in this case, accept the dominasion as well as agree the discourse that they should work in domestic area. This is called as a symbolic violence to the women.